2015
DOI: 10.1038/bmt.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6 encephalitis after allogeneic hematopoietic cell transplantation: What we do and do not know

Abstract: Human herpesvirus-6 (HHV-6) encephalitis following allogeneic hematopoietic cell transplantation is a serious and often fatal complication accompanying reactivation of HHV-6B. Incidence varies among studies, but is reportedly 0-11.6% after bone marrow or PBSC transplantation and 4.9-21.4% after umbilical cord blood transplantation, typically around 2-6 weeks post transplant. Symptoms are characterized by memory loss, loss of consciousness and seizures. Magnetic resonance imaging (MRI) typically shows bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 92 publications
3
92
0
1
Order By: Relevance
“…Since 2008, preemptive therapy was started when HHV-6 DNA exceeded 125 copies/mL to prevent encephalitis. However, previous trials suggested HHV-6 DNA-guided preemptive therapy was inadequate in preventing HHV-6 encephalitis [24,32,33]. Further studies are needed to prove efficacy of preemptive therapy of HHV-6 encephalitis.…”
Section: Discussionmentioning
confidence: 95%
“…Since 2008, preemptive therapy was started when HHV-6 DNA exceeded 125 copies/mL to prevent encephalitis. However, previous trials suggested HHV-6 DNA-guided preemptive therapy was inadequate in preventing HHV-6 encephalitis [24,32,33]. Further studies are needed to prove efficacy of preemptive therapy of HHV-6 encephalitis.…”
Section: Discussionmentioning
confidence: 95%
“…13 HHV-6 encephalitis is therefore increasingly recognized as an important complication of allo-HSCT; however, many questions remain unanswered. Reported incidence of HHV-6 encephalitis among allo-HSCT recipients ranges from 0.96 to 11.6%, 5 mainly owing to small cohorts of cases. Although umbilical cord blood transplantation (CBT) represents a risk factor for HHV-6 encephalitis, 5,12,14 other risk factors remain unconfirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Reported incidence of HHV-6 encephalitis among allo-HSCT recipients ranges from 0.96 to 11.6%, 5 mainly owing to small cohorts of cases. Although umbilical cord blood transplantation (CBT) represents a risk factor for HHV-6 encephalitis, 5,12,14 other risk factors remain unconfirmed. Treatment recommendations have been made based on in vitro data, [15][16][17] but few data are available on the clinical effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…HHV-6 reactivation facilitates transactivation of other herpesviruses, such as HHV-7 or human cytomegalovirus (HCMV) , and the spread of fungal infections (6)(7)(8)(9)(10). Interestingly, for several chronic neurological disorders such as multiple sclerosis (MS), Alzheimer's disease (AD), or chronic fatigue syndrome (CFS), markedly elevated HHV-6 titers were determined (11)(12)(13). Yet, whether HHV-6 has a causative role in these diseases or whether reactivation is a consequence of a deregulated and malfunctioning immune system requires elucidation.…”
mentioning
confidence: 99%